LITERASI DAN NASKAH ULU ABAD XX PADA BERBAGAI KELOMPOK ETNIK DI BENGKULU - Ngudining Rahayu (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
AbstractThis research aims to explain the literacy Ulu and the function of the manuscripts in the context of socio-cultural communication in a variety of ethnic group in Bengkulu at the beginning oh the twentieth century.  The research based on survey of the Ulu literacy regarding a various ethnic groups in Bengkulu, and on discourse and practice of selected manuscripts preserved at the State Museum of Bengkulu, RUB (Royal Netherlands University Library) Leiden, KITLV (Royal Netherlands Institute of Southeast Asia and Caribbean Studies) Leiden, the National Library of Republic Indonesia, and the manuscripts preserved as families or villages heirlooms in several villages in Bengkulu Province as well.   The results of the research shows as follows: (1) at that time the number of literate people slightly, about 1 to 200 in Serawai ethnic group, 1 to 431 in Rejang ethnic group, and less on the others; nevertheles, the Ulu literacy amongs a variety of ethnic groups in Bengkulu at that time idicate the level of functional literacy; (2) generally they also literate in Jawi and Arabic script and mastered the cultural knowledge from the origin of Jawi and Arabic script as well; (3) the literate people are able to read and understand the text well and write texts of cultural knowledge and social practices; (4) they write texts related to social status and their role in society; in such condition, the Ulu manuscripts is a medium to represent, transform, and cunstruct the cultural knowledge and social practice